Political prisoners and repression in India. - South Asia Students Association; Committee for Human Rights India Forum; Spark:::Creator::::::::::::
Promotional Poster for a talk given by Mary Tyler, a British school teacher and chairperson of the "Alliance Against Fascist Dictatorship in India," on her experiences being imprisoned in India for five years. The talk was accompanied by a slide show by the Committee for Human Rights and a documentary film entitled: Calcutta.